Comparison of Compositional Changes in Multi-Species Grass/Legume Mixture Experiments Across Three Nordic Countries (Iceland, Sweden and Finland) Over Two Years - Brophy, Caroline; Gustavsson, Anne-Maj; Helgadottir, A.; Nissinen, Oiva; Connolly, J. (UKnowledge, 2023)
A multi-site experiment was established at 39 sites across Europe, Australia and Canada within COST Action 852 to: (1) assess the benefits of grass/legume mixtures over monocultures, (2) test the stability of mixtures and (3) evaluate the consistency of the observed patterns over broad environmental gradients. This paper compares the results from 3 Nordic sites using the same plant species: Korpa Experimental Station in Iceland, Lapland Research Station in Finland and Piteå in Sweden to investigate if compositional changes in mixtures are consistent across the sites.